The impact of cement on argillaceous rocks in radioactive waste disposal systems: A review focusing on key processes and remaining issues. (July 2021) - Wilson, James; Bateman, Keith; Tachi, Yukio
Abstract: Several repository concepts have been proposed for the disposal of radioactive wastes, some of which include argillaceous (clay-rich) host rocks and cementitious engineered barriers. The presence of hyperalkaline cement pore-fluid results in the destabilization of primary minerals in argillaceous rocks, leading to alteration at the interface between cement/concrete and repository host rock. This phenomenon has implications for radionuclide transport and safety assessment. Data on cement-mudrock interactions from experimental, analogue, and modelling studies have been reviewed, and remaining areas of uncertainty identified. Although a reasonably good understanding of the key processes has been acquired, there are some areas in which uncertainty remains, in particular: system evolution at temperatures above 25 °C; the kinetics of secondary mineral growth; the extent of pore-clogging due to secondary mineral formation; the degree to which predicted porosity reduction could impede contaminant migration; and the effect of host rock alteration on contaminant sorption. A multi-disciplinary programme of work is likely to be the most productive to elucidate further the key processes and how they operate over different spatial and temporal scales. The ongoing acquisition of geochemical data for model construction, and the testing of geochemical models against analogue and laboratory data, should reduce some of the uncertainties associated with predicting repository evolution, thereby aiding safety case development. Highlights: Deep geological disposal is widely recognized as the preferred option for managing long-lived radioactive wastes. Many repository concepts include cementitious barrier materials and clay-rich host rocks. Available data suggest that a zone of alteration will form at cement-mudrock interfaces (with implications for contaminant transport). Remaining uncertainties include: repository evolution at T > 25 °C; rates of secondary mineral growth; porosity evolution (and its implications). Further work to address these uncertainties will aid the development of safety assessments for radioactive waste disposal facilities.